FIRST POSNER SCHLOSSMAN SYNDROME POST COVID-19 INFECTION - Kristian Goenawan; Margrette Paliyama (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: We reported a unique case report of Posner Schlossman Syndrome (PSS) after Covid-19 infection. Case Illustration: Female 54 y.o. came in our hospital with chief complaint of painless blurred vision, red eye, and very high pressure on right eye (RE). She had the same complaint 1½ months before and diagnosed as acute primary angle closure glaucoma (PACG), treated successfully with good outcome. She also had history of covid-19 infection 1 month before the first attack. Initial visual acuity (VA) of RE is 20/70. Anterior segment showed mild inflammation with flare and cell but no KP, while posterior segment cannot be assessed. IOP was 57.0 mmHg. After 1 month of medication (patient rejected to go inward), the patient finally agreed to the trabeculectomy because VA decreased to 20/200. Perimetry and OCT has been done before the operation, showed decreased parameter. One day, 7-days, and 28-days post operated VA were 3/60, 20/50, and 20/40 respectively, while IOP were 9.0 mmHg, 6.7 mmHg, and 15.0 mmHg respectively. Discussion: PSS can be very similar to acute PACG, though with careful history taking and examination we can distinct the disease. History taking for recurrent attack and unilateral is very important. Examination that showed acute open angle marked IOP with sign of uveitis should lead to PSS. Conclusion: In every attack of glaucoma, PSS has resemblance with acute PACG. The foresight of an ophthalmologist in determining the diagnosis is indeed very important.